Оценка воздействия выбросов автотранспортных средств в окружающую среду Республики Каракалпакстан (SCIENCE and SOCIETY, 2025)
The article discusses the issues of comparative assessment of the impact of vehicle emissions into the environment of the northern and southern regions of the Republic of Karakalpakstan. When assessing the levels of atmos- pheric air pollution in certain territories, the highest proportion of non-standard samples was recorded in the Northern and Southern regions of the Republic of Karakalpakstan. It is important to implement technical solutions aimed at improving